Metagenomic Analysis Revealed Differences in Composition and Function Between Liquid-Associated and Solid-Associated Microorganisms of Sheep Rumen - Su, Manchun; Hao, Ziyun; Shi, Huibin; Li, Taotao; Wang, Huihui; Li, Qiao; Zhang, Yong; Ma, Youji (Frontiers in Microbiology, 2022)
The rumen microbiota plays a key role in the utilization of plant materials by ruminants, yet little is known about the key taxa and their genetic functions of the rumen sub-environment involved in the ruminal degradation process. Understanding the differences in the composition and function of ruminal microbiota in the liquid-associated (LA) and solid-associated (SA) systems is needed to further study and regulate rumen function and health. In this study, rumen contents of nine sheep were collected to separate LA and SA systems with elution and centrifugal precipitation. Metagenome sequencing was used to investigate the differences in microbial composition and genetic functions of LA and SA systems, with special emphasis on their degradational potential toward carbohydrates. Results showed that the dominant species composition was similar between the two systems, but SA microorganisms had a higher relative abundance than LA microorganisms in all taxa. The concentration of fiber-degrading bacteria, such as Ruminococcus, Treponema, and Fibrobacter, was higher and Prevotella was lower in the SA vs. LA system. Additionally, SA microorganisms dominated in cellulose degradation, while LA microorganisms were more important in starch utilization based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) Orthology (KO)'s functional categories and Carbohydrate-Active Enzymes (CAZymes). In general, SA microorganisms are more abundant and important in metabolic functions than LA, such as carbohydrate and amino acid metabolisms. In summary, the key differential biomarkers between LA and SA systems were Prevotella, Ruminococcus, Treponema, and Fibrobacter. Ruminal microbes degraded carbohydrates synergistically with SA, thus, more focusing on cellulose and hemicellulose, while LA is more important to starch.